DETERMINAÇÃO DOS CARACTERES ADAPTATIVOS E COMPONENTES DO RACEMO EM CULTIVARES DE MAMONA - Bandeira, Taiane P.; Silva, Adair J. d.; Gaviraghi, Juliano; Fontaniva, Cristiano; Arenhardt, Emílio G.; Oliveira, Juliana M. d.; Krüger, Cleusa A. M. B.; Carbonera, Roberto; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo